2022
DOI: 10.1111/aji.13523
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin regulates trophoblast pyroptosis, invasion and migration in preeclampsia by inhibiting HtrA1 transcription through the microRNA‐520c‐3p/SETD7 axis

Abstract: Objective Melatonin has an inhibitory effect on preeclampsia (PE). This study was launched to explore the way that melatonin regulated trophoblast migration, invasion, and pyroptosis in PE and to provide new ideas for the diagnosis and treatment of PE. Methods Expression levels of melatonin receptors (MT1 and MT2), microRNA (miR)‐520c‐3p, SETD7, and HtrA1 in placental tissues and HTR8/SVneo cells were measured by RT‐qPCR and Western blot. Scratch, Transwell, and Western blot assays were performed to detect mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The role of HTRA1 in HTR8/SVneo cell invasion and motility is still a matter of debate. In fact, few studies reported a decreased migration and invasion when HTRA1 was up-regulated by specific plasmids [18,39,40]. Another study reported a significant increase in HTR8/SVneo cell invasion when HTRA1 was overexpressed [41].…”
Section: Discussionmentioning
confidence: 99%
“…The role of HTRA1 in HTR8/SVneo cell invasion and motility is still a matter of debate. In fact, few studies reported a decreased migration and invasion when HTRA1 was up-regulated by specific plasmids [18,39,40]. Another study reported a significant increase in HTR8/SVneo cell invasion when HTRA1 was overexpressed [41].…”
Section: Discussionmentioning
confidence: 99%
“…The downregulated LINC00240 aggravates oxidative stress-induced pyroptosis through increasing miR-155 and reducing Nrf2 expression, and LINC00240 overexpression mitigates the pyroptotic death of trophoblasts (58). Additionally, the lowlyexpressed miR-520c-3p is observed in the placental tissues of PE patients and H/R-treated trophoblasts, and melatonin may suppress trophoblasts pyroptosis via modulating miR-520c-3p/SETD7 axis (93). Taken together, these ncRNAs are expected to be possible therapeutic targets for APS-correlated APOs treatment Recently, trophoblasts pyroptosis has been reported to be modulated by glycolytic enzymes, showing the tightly relation of cellular pyroptosis with metabolic phenotypes.…”
Section: The Role Of Pyroptosis In Trophoblastsmentioning
confidence: 98%
“…Excessive apoptosis is closely related to PE, and can be partly reversed by treatments like aspirin, cyclosporine A and resveratrol [ 132 134 ]. Pyroptosis in trophoblast cells promotes the occurrence and development of PE [ 135 ]. Some studies have confirmed that pyroptosis occurs in trophoblasts of women with early-onset PE, as evidenced by elevated levels of active caspase-1, GSDMD, IL-1β, and IL-18 [ 42 , 136 , 137 ].…”
Section: Rcd In Different Pregnancy Complicationsmentioning
confidence: 99%